Relationships between docility and reproduction in Angus heifers - White, Kari L.; Bormann, Jennifer M.; Olson, K. C.; Jaeger, John R.; Johnson, Sandra K.; Downey, B.; Grieger, David M.; Waggoner, Justin W.; Moser, Daniel W.; Weaber, Robert L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Reproductive success is relevant in beef cattle operations because income generated by the sale of calves is often a large portion of an operation’s income. Selecting for fertility is difficult because it is influenced by a variety of factors. Temperament could be a factor affecting fertility. Physiological responses associated with temperament can influence the probability of cows becoming pregnant because stress hormones in the bloodstream can negatively affect the release of reproductive hormones. Methods have been developed to assess temperament in cattle. Exit velocity measures the time it takes for an animal to cover a predetermined distance after vacating a chute. Chute scores range from 1 (quiet) to 6 (aggressive) and are based on the animal’s behavior when confined in a chute. Positive correlations of chute score and exit velocity with cortisol indicate that both scores are reliable indicators of temperament. Handling of cattle is associated with changes in concentrations of stress hormones. Blood serum collection can provide insight into short-term stressors, and fecal sampling can be reflective of stress experienced 2–3 days before sampling. This study was conducted to investigate the relationship between animal temperament and heifer fertility as indicated by first-service artificial insemination conception rate.
Keywords: Beef; Beef cattle; Fertility; Temperment; Stress